Inventory Routing Problem for Perishable Product with Dynamic Demand and Spoilage Rate - Krisna Wahyudi; I Gede Agus Widyadana; I Nyoman Sutapa (International Journal of Industrial Research and Applied Engineering, 2021)
The paper presents an inventory routing problem for perishable products using dynamic demand and spoilage rate data. This problem has three main costs for the simulation criteria: holding inventory cost, routing shipment cost, and perishable product cost with a single supplier and many retailers. Instead of the problem, there are 2 set decision variables inventory level range and shipping route. The simulation uses a Genetic Algorithm method to find the minimum cost. It shows that the dynamic data demand can be optimized, and the dynamic demand data have bigger cost consequences than the static demand data